Does breast density measured through population-based screening independently increase breast cancer risk in Asian females? - Park, Boyoung; Cho, Hye Mi; Lee, Eun Hye; Song, Seunghoon; Suh, Mina; Choi, Kui Son; Kang, Bong Joo; Ko, Kyungran; Yi, Ann; Jung, Hae Kyoung; Cha, Joo Hee; Jun, Jae Kwan (Clinical Epidemiology, 2018)
The purpose of this study was to investigate the effects of breast density on breast cancer risk among women screened via a nationwide mammographic screening program. We conducted a nested case-control study for a randomly selected population of 1,561 breast cancer patients and 6,002 matched controls from the National Cancer Screening Program. Breast density was measured and recorded by two independent radiologists using the Breast Imaging Reporting and Data System (BI-RADS). Associations between BI-RADS density and breast cancer risk were evaluated according to screening results, time elapsed since receiving non-recall results, age, and menopausal status after adjusting for possible covariates. Breast cancer risk for women with extremely dense breasts was five times higher (adjusted odds ratio [aOR] =5.0; 95% confidence interval [CI]) =3.7-6.7) than that for women with an almost entirely fatty breast, although the risk differed between recalled women (aOR =3.3, 95% CI =2.3-3.6) and women with non-recalled results (aOR =12.1, 95% CI =6.3-23.3, -heterogeneity =0.001). aORs for BI-RADS categories of breast density were similar when subjects who developed cancer after showing non-recall findings during initial screening were grouped according to time until cancer diagnosis thereafter (<1 and ≥1 year). The prevalence of dense breasts was higher in younger women, and the association between a denser breast and breast cancer was stronger in younger women (heterogeneously dense breast: aOR =7.0, 95% CI =2.4-20.3, women in their 40s) than older women (aOR =2.5, 95% CI =1.1-6.0, women in their 70s or more). In addition, while the positive association remained, irrespective of menopausal status, the effect of a dense breast on breast cancer risk was stronger in premenopausal women. This study confirmed an increased risk of breast cancer with greater breast density in Korean women which was consistent regardless of BI-RADS assessment category, time interval after initially non-recall results, and menopausal status.